Determination of Ammonia Level and Its Protein Conversion in the Water of Biofloc Fish Farming Technology - Ghimire, Rishi Ram; Ghimire, Anjila; Karki, Dilip; Basyal, Durga; Rai, Krishna Bahadur (Prithvi Academic Journal, 2023)
The biofloc system is a wastewater treatment technology and is used for fish farming by creating the artificial environment. Biofloc Technology (BFT) can enhance the water quality in aquaculture that introduces natural nutrient recycling characteristics with the induction of appropriate Carbon/Nitrogen (C/N) ratio. This study aimed to estimate the effect of BFT implementation on the water quality and production performance of common carp fishes using different concentration of carbon and to attempt a treatment of excess ammonia. The experiment was performed in four tanks (T1, T2, T3 and T4) containing the 10000 liter of water and 5000 shrimps on each tank that has a five weeks’ experimental treatment by adding the carbon as (25%, 30%, 35%, 40% and 45% of sugar) according to its feeding diet from sugar in the interval of one week. The ammonia level before and after the treatment with respect to the percentage of carbon from sugar addition on BFT signifies that the 40% of carbon (C:N ratio of 20:1) and 45% of carbon (C:N ratio of 23:1) have a better performance on the ammonia treatment than 25%, 30% and 35% of carbon. The change in the water's color from green to brownish indicates the protein conversion of ammonia, which informs that the water becomes higher in quality after treatment than it was before for the biofloc fish farming system. It also provides an information about the nitrification process that takes place when the water is treated with carbon derived from sugar. The findings of this study have important implications for the improvement of biofloc fish farming systems.